The Role of Food Vlogger @Gilangaditja in Encouraging Consumers to Buy Products - Muhammad Septian Nurrizal; M. Aurel Saputra Yudha; Farida Nurfalah; Abdul Jalil Hermawan (CV. Media Digital Publikasi Indonesia, 2025)
The development of digital technology and the popularity of video sharing platforms such as YouTube, TikTok, and Instagram have encouraged the emergence of food vloggers as influential figures in the culinary world. This study aims to analyze the role of food vlogger @gilangaditja to invite consumers to buy products on the Instagram platform, especially in the Cirebon area. Using a case study-based qualitative approach, data was collected through observation of Instagram content and analyzed by applying the theory of source credibility proposed by Hovland, Janis, and Kelley, as well as the theory of content marketing and consumer behavior. The research revealed that @gilangaditja succeeded in building an image through competence, trustworthiness, and personal appeal. The content produced is informative, interesting, and emotional, thus creating a strong persuasive influence on the audience. The high level of intensive interaction and testimonials from followers shows that food vloggers can act as significant content creators to encourage consumers to buy products. These findings suggest that culinary industry players can utilize collaboration with food vloggers as an important element in an effective digital marketing strategy.